Bacteremia in Diarrheal Children With Severe Pneumonia. (July 2019) - Saha, Haimanti; Shahrin, Lubaba; Sarmin, Monira; Ahmed, Tahmeed; Chisti, Mohammod Jobayer
Objectives . Diarrhea and pneumonia are the leading causes of under-5 childhood mortality. However, there is limited information on bacterial etiology of severe pneumonia in children with diarrhea. We analyzed bacterial pathogens from the blood of children under the age of 5 years. Methods . In this retrospective cross-sectional study, we studied all children having severe pneumonia with or without diarrhea admitted to the icddr, b (International Centre for Diarrheal Disease Research, Bangladesh) who had their blood culture done during January 2014 to December 2014. Results . Among a total of 159 study children, 118 had diarrhea. There were 13 bacterial isolates, and predominant organisms were gram-negative bacteria (11/13, 85%). Children with diarrhea coexisting with severe pneumonia proportionately had higher bacteremia (12/141 [10.16%] vs 1/41 [2.43%]), but the difference was not statistically insignificant ( P = .186). Conclusion . We recognized that the coexistence of diarrhea and severe pneumonia had proportionately higher bacteremia, especially gram-negative bacteria compared with those without diarrhea. The results emphasize the trend of bacterial etiology of pneumonia in children with diarrhea and may warrant revised antibiotics guideline for their management.